Strategy To Get Better Consumers Via The Tiktok Application For Beauty Products - rofiah, chusnul (Magister Manajemen of Universitas Islam Nahdlatul Ulama Jepara, 2024)
The aim of this research is to help business people better understand the benefits of the phenomenon of marketing content, copywriting and information credibility which is considered one of the main effects that will ultimately lead to increased sales as well as efforts to optimize marketing strategies that have experienced developments, from traditional marketing methods. to modern marketing methods. The focus is to understand the impact and popularity of the TikTok platform which has 1.1 billion followers and how the platform has become relatively more popular compared to competitors on the same platform since it was first founded in 2019. TikTok has become one of the social media platforms that is currently trending with interesting content in the application. Scarlett Whitening is one of the most viewed brands on the app. This research aims to better understand the influence of marketing content, copywriting and the credibility of information through the TikTok application on purchasing decisions for Scarlett Whitening. To understand the effect, we apply the information adoption model because it has been widely used in previous research. Variable amount of information added to the information use model. We collected data from 403 respondents via a Google Form survey which had several criteria. PLS-SEM uses selected Smart PLS to analyze the data. We found that the application of information has a positive and significant effect on purchase intention. The model was able to accurately predict Scarlett Whitening's purchase intentions by 21.1%.